Delisted versus voluntary delisted versus remain listed: financial disclosure timing - D. Balios; N. Eriotis; S. Missiakoulis; D. Vasiliou (Applied Economics Letters, 2016)
We focus in the period of announcement of accounting information for companies listed in an organized market and we re-examine their probability of delisting, voluntarily or not. Adopting the same framework, consideration is given to the assumption that investors utilize market information when accounting data are published. The analysis provided indicates that investors should pay attention to the financial disclosure timing. Our investigation demonstrated that even the short period of three months is quite important to making investment decisions.